Synthesis, Biological Activity and Molecular Docking Studies of Heterocyclic Chalcones. Issue 9 (26th August 2022) - Kamra, Nisha; Rani, Suman; Thakral, Sumit; Singh, Ajeet; Sangwan, Payare L.; Singh, Shashank K.; Thakral, Samridhi; Singh, Vikramjeet; Kumar, Devinder
Abstract: Nineteen heterocyclic chalcones were synthesized from 4‐acetyl‐5‐methylquinolylpyrazole and heteroaryl (imidazole, pyrazole, thiophene, indole and triazole) aldehydes and were screened in vitro using four tumor cell lines for their cytotoxic capability and for antimicrobial activity. The chalcone 5b exhibited the highest activity with IC50 values 2.14 μM against colon (HCT‐116) and 5.0 μM, against prostate (PC‐3) cancer cell lines and also displayed good activity against fungal strain ( A. niger ) with MIC value 9.1 μM. The chalcones 5q and 5p displayed good activity against bacterial strains ( S. aureus ) having MIC value 2.6 μM and fungal strain ( C. albicans ) having MIC value 5.4 μM, respectively. The molecular docking outcome revealed that the synthesized heterocyclic chalcones demonstrated hydrogen bond, hydrophobic and electrostatic interactions with their respective biochemical targets. Abstract :